Age-dependent changes in biometrics indicate senescence in the European Blackbird Turdus merula. Issue 2 (3rd April 2018) - Piliczewski, Piotr; Jankowiak, Łukasz; Wysocki, Dariusz
ABSTRACT: Capsule: A 19-year study of European Blackbirds Turdus merula confirms that senescence is associated with a decrease in condition measured by wing length but bills become progressively longer with age. Aims: To explore the correlations between biometrics of Blackbirds and age, to identify possible links with senescence. Methods: During the 19 years of the study, 801 birds of known age were measured: 431 males and 370 females, aged from 2 to 10 years. Among these 91 males and 50 females were retrapped at least one moult later. For each bird, there were at least one set of measurements when fully grown. Results: Wing length increased until the sixth year of life after which it started to decrease. An increase in bill length throughout the lifetime was found in both sexes. Conclusion: Changes in wing length correspond with an earlier study of this population suggesting the onset of senescence after the fifth to sixth calendar year of life.